Physiological Study about Rosuvastatin and Lovastatin as Compared with Quercetin in Rats (Rattus norvegicus) - Wissam Sajid Hashim (Journal of Global Pharma Technology, 2016)
The present study was accomplished to compare the role of the flavonoid quercetin with some antihyperlipidemic drugs rosuvastatin and lovastatin on lipid profile and other serum parameters of rats. In this study, five groups of eight male rats each were used. The groups were allocated as: control, cholesterol, rosuvastatin, lovastatin and quercetin groups. The animals of the control group were maintained on standard diet, while other groups were maintained on cholesterol diet 15mg/kg of diet and dosed orally and daily as follow: rosuvastatin 20 mg/kg body weight, lovastatin 15 mg, and quercetin 100 mg respectively. The results revealed that rosuvastatin and lovastatin could lower lipid profile but still significantly higher than control group while quercetin lowers them without significant difference with control. The liver enzymes were elevated by statins and they were normal and without significant difference in case of quercetin comparing with control group at (P≤0.05).Key words: Quercetin, Rosuvastatin, Lovastatin, Lipid, Rats.